PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK TERPADU TEMA BERBAGAI PEKERJAAN - abdul Waris (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study aims to determine whether the application of Number Head Together type of cooperative learning can improve Integrated Thematic Learning Outcomes on the Theme of Various Jobs for Fourth Grade Students of UPTD SD Negeri 136 Barru in Semester One of the Academic Year 2021/2022. The subjects in this study were 23 fourth grade students. The indicator of research success is an increase in students' ability to understand the themes of various jobs which can be seen in the final grades in each cycle where the average student achievement increases. After taking action in the form of implementing cooperative learning with the Number Head Together type, the average final score in the first cycle was 83.3 or in the good category and an increase in the second cycle was 85.3 where 78.26% of students reached the very good category, 21.74% of students achieved good category. The results showed that the application of Number Head Together type of cooperative learning can improve the Integrated Thematic Learning Outcomes in Various Jobs for the fourth grade students of UPTD SD Negeri 136 Barru.